Mode-Locked Erbium-Doped Fiber Laser Using Vanadium Oxide as Saturable Absorber - Nady, Ahmed; Baharom, Mohd Faizal; Latiff, Anas Abdul; Harun, Sulaiman Wadi (IOP Publishing, 2018)
A mode-locked erbium doped fiber laser (EDFL) is demonstrated using the vanadium oxide (V 2 O 5 ) material as a saturable absorber (SA). The V 2 O 5 based SA is hosted into poly ethylene oxide film and attached on fiber ferule in the laser cavity. It shows 7% modulation depth with 71MW/cm2 saturation intensity. By incorporating the SA inside the EDFL cavity with managed intra-cavity dispersion, ultrashort soliton pulses are successfully generated with a full width at half maximum of 3.14 ps. The laser operated at central wavelength of 1559.25nm and repetition frequency of 1 MHz.